Review: Improving global food security through accelerated plant breeding - Lenaerts, Bert; Collard, Bertrand C. Y.; Demont, Matty (Elsevier, 2019)
With an expected 9 billion people by 2050 and average income on the rise in the developing world, meeting future food demand will be a challenge. Climate change, urbanisation and land degradation are putting further pressure on the food supply. The multifaceted and self-reinforcing nature of these challenges calls for a fundamental transformation of the food system. In the past, crop improvement through breeding has been the major tool to lift people out of poverty and increase global food supply. To adequately address these food security challenges, new improved crop varieties need to be developed and reach farmers sooner as a partial solution. In this review, we focus on various proven conventional and biotechnological accelerating plant breeding methods that do not require genetic engineering or gene editing. We pay specific attention to the feasibility for implementation by national agricultural research systems in developing countries in the short term. We argue that postponing technologies that can accelerate breeding makes no economic sense and warrant immediate adoption of accelerated breeding practices in the public sector. Considering a wide range of factors including the economics of accelerated breeding, we advocate the use of a method called rapid generation advance (RGA) as the most feasible method for accelerating breeding in the public sector